Remembering enslavement reassembling the Southern plantation museum - Potter, Amy E.; Hanna, Stephen P.; Alderman, Derek H. 1968-; Carter, Perry L.; Bright, Candace Forbes 1985-; Butler, David L. (The University of Georgia Press, 2022)
"Remembering enslavement explores plantation museums as sites for contesting and reforming public interpretations of slavery in the American South."--Back cover
Keywords: Geschichte; Kollektives Gedächtnis; Museum; Plantage; Sklaverei; USA -- Südstaaten; Historical museums / Southern States; Slavery / Southern States / Historiography; Plantation life / Southern States / Historiography; Historic sites / Southern States; Histoire / Musées / États-Unis (Sud); Vie dans les plantations / États-Unis (Sud) / Historiographie; Lieux historiques / États-Unis (Sud); Historic sites; Historical museums; Plantation life / Historiography; Slavery / Historiography; Southern States